Working mode detection method based on bidirectional LSTM for pipe jacking inertial automatic guidance system - Yutong Zu; Lu Wang; Yuanbiao Hu; Gansheng Yang; Boning He; Zheng Zhou (Scientific Reports)
Abstract The pipe-jacking inertial guidance method is a key technology to solve the guidance problems of complex pipe-jacking projects, such as long distances and curves. However, since its guidance information is obtained by gyroscope integration, the accrued error is significant, which limits its application. The pipe-jacking construction process has two working modes of static and jacking. The accumulated errors of static state can be corrected with zero velocity to suppress the system position dispersion. Therefore, zero-velocity detection is required. However, the pipe-jacking velocity is so slow (1–2 m/h) that the traditional threshold-based zero-velocity detection method cannot accurately detect the zero-velocity interval (ZVI). Bidirectional long short term memory (Bi-LSTM) can effectively extract the features of repetitive and regular movements during the long-time pipe-jacking construction process. Therefore, this research proposes a working pattern detection model for pipe-jacking based on Bi-LSTM deep learning framework. Through establishing a data collection system to construct the data set and training the model, the accuracy of the test set reaches 98.54%. In addition, a zero-velocity correction model is established. According to the zero-velocity detection results of the Bi-LSTM model, zero-velocity correction is performed. Subsequently, an experimental platform is established to simulate a curve pipe-jacking and attitude experiments. The attitude experiment proves that the proposed model detects the ZVI accurately. The inclination error is corrected by 0.06 °, and the azimuth error is corrected by 0.18 °. Finally, the proposed model is validated by the crossing project of the China-Russia Eastern Natural Gas Pipeline, and the results show that the proposed model effectively detects the working pattern of pipe-jacking machine with strong robustness and adaptability. In summary, the method can effectively improve the detection accuracy of the pipe-jacking working pattern. It lays the foundation for the application of the inertial guidance system in complex pipe-jacking, such as long-distance and curved projects.